Application of the one‐minute preceptor technique by novice teachers in the gross anatomy laboratory. Issue 6 (8th January 2015) - Chan, Lap Ki; Yang, Jian; Irby, David M.
Abstract : The one‐minute preceptor (OMP) was originally developed in the ambulatory care setting as a time‐efficient teaching technique for learner‐centered clinical training. There are also possible advantages of using the OMP in the gross anatomy laboratory. However, in a previous study it was found that providing training to experienced gross anatomy teachers in the use of the OMP did not result in improvement in students' perceptions of their learning, probably because of the fact that the experienced teachers had already developed their own pedagogical approaches. In the current study, we examined the effects of training novice teachers with about four years of gross anatomy teaching experience, in the use of the OMP in the gross anatomy laboratory, by surveying students to collect their views on their learning experiences, by observing the teachers' teaching behaviors before and after they were trained in OMP, and then by interviewing them. More students reported a better learning experience in the session after the teachers had been trained in the OMP than reported worse, in eight out of the nine items related to their learning experiences. The novice teachers were receptive to the OMP. After the OMP training, the novice teachers were observed to engage more in getting commitments from the students and in reinforcing what the students have done right, two of the five OMP microskills. They considered the OMP to be very useful for their development as anatomy teachers. Anat Sci Educ 8: 539–546. © 2015 American Association of Anatomists.